Use of Silica Fume, Bentonite, and Waste Tire Rubber as Impermeable Layer Construction Materials - Ahmet Şenol; Arzu Guner (Advances in Civil Engineering)
To avoid the potential risks associated with all hazardous wastes, it is important that containment methods are intended to prevent the migration of liquid hazardous wastes or leaks containing hazardous components. Therefore, impermeable barriers were used to prevent contamination. In this study, geotechnical tests were performed on samples by mixing rubber and bentonite with silica fume at certain percentages. The aim of the experimental studies is to evaluate the applicability of certain proportions of silica fume, rubber, and bentonite mixtures as impermeable liner material. Possible cracks in bentonite during drying are reduced by the use of silica fume. Absorption of dynamic effects that may occur on the impermeable barrier layer is achieved by adding waste rubber in a uniform size. Several geotechnical tests were performed to examine the mixed rubber and bentonite with silica fumes. Looking at the results of the whole that mixed rubber and bentonite with silica fume yielded usable results and a blend for construction of a liner.